School Principal's Strategy in Improving Teacher Motivation, Competence, and Performance - Rahayu Mardikanningsih; Chelsea Zahra Auliya; Ningrum Fadilaturrohmah; Didit Darmawan; Mila Hariani (Civiliza Publishing, Indonesia., 2026)
The quality of education in education units is highly determined by the performance of teachers which is influenced by their motivation and competence. The principal has a strategic role to create conditions that allow the improvement of these three aspects simultaneously and integrated. This study aims to examine strategies that can be applied by school principals to improve teacher motivation, competence, and performance, as well as analyze how to implement these strategies effectively. The method used in this study is a literature study that collects and analyzes various sources of information relevant to the topic of the study. The results of the study show that strategies that can be implemented include giving recognition and awards, providing opportunities to participate in decision-making, preparing professional development programs, assigning appropriate tasks, creating a conducive work environment, and implementing an objective performance appraisal system. The implementation of this strategy in an integrated and sustainable manner will provide optimal results to improve the quality of human resources in schools. The implication of this study is the need to develop the leadership skills of school principals that focus on developing human resources to achieve the expected educational goals.